TRANSLATION AS IMPERIALISM: THE LAST OF THE MOHICANS - Subur Wardoyo (Celt: A Journal of Culture, English Language Teaching & Literature, 2002)
In this article translation is not only confined to the linguist, but also to all strategies that represent a language to another language. The way James Fenimore Cooper translated the Indian language to English in the novel The Last of The Mohicans shows a representation of ethnic harassment manipulation of language. Cooper's translation build up the suggestion that Indians can only communicate only like children. The Indians are portrayed to only communicate by playing with their voice, music, gesture, and using the third-person pronoun to exchange dor the first-person or second-person pronoun. This harassment is correlated with the policy of Indian removal at that era